USULAN PEMILIHAN ALTERNATIF TIPE CRANE BERDASARKAN FAKTOR BIAYA DAN FISIK DI PT. XYZ - Pandapotan Simarmata; Abadi Ginting (Jurnal Teknik Industri USU, 2013)
PT XYZ is a company concerned in the port services, one of which is the loading/unloading of goods using a mobile crane. Based on observations, a mobile crane company owned only one unit and installed capacity company are 92 tons per hour company while the load demand on average 157 tons per hour. From the above data shows that the company can not meet the load demand due to insufficient capacity. In an attempt to adjust the loading capacity and load demand is done with addition of capacity through addition of crane. Forecasting is used as a method to predict the loading demand in the future. Data of forecasting is used as reference in approximating the exact number of cranes. Based on the calculations, crane that needed to solve the problem are two units, so it required the addition one crane. The proposed alternative type of cranes are mobile crane 5 ton capacity and luffing crane 10 tons capacity. The best type of crane are selected using decision theory which use payoff approach, they are payoff profit and payoff risk. From the calculation, the best type of alternative criteria from the payoff profit is Luffing crane with a value 7.75, 10, 2.5, 2.5, while for the payoff risk, the best is mobile crane with a value 4.55; 3.5; 7; 1,75. The best type of crane based on comparative payoff is luffing crane. With the addition of luffing crane loading capacity of 10 tons to 276 tons of companies per hour and can meet the load demand loading/unloading and companies.